Maternal Mortality in Dodoma Regional Referral Hospital, Tanzania - Mzee M. Nassoro; Paul Chetto; Enid Chiwanga; Athanase Lilungulu; Deogratius Bintabara; Jacquiline Wambura (Hindawi Limited, 2020)
Background. Maternal mortality has remained a challenge in Tanzania. The Tanzania Demographic and Health Survey 2015-16 has shown that the problem has been increasing despite various strategies instituted to curb it. It has been shown that most of the maternal deaths occurring in health facilities, whether direct or indirect, have other contributing factors. The objective of this study was to analyse causes and associated factors for maternal deaths in Dodoma Regional Referral Hospital (DRRH). Methods. A retrospective review of all files of the women who died in 2018 and were classified as maternal deaths. Results. A total of 8722 women gave birth in DRRH, out of which 35 died and were confirmed as maternal deaths. The number of live births was 8404 making the maternal mortality ratio of 417 per 100,000 live births. The leading causes of maternal death were eclampsia (9), sepsis (6), ruptured uterus (5), and haemorrhage (5). The third-phase delay was the leading contributing factor to 19 maternal deaths. This includes delays in referral from another facility as well as delays in getting treatment at DRRH and inadequate skills of providers at both the referring facilities and DRRH. The first-phase and second-phase delays contributed to 7 and 6 deaths, respectively. Furthermore, poor antenatal care contributed to 2 deaths. Conclusion. Maternal mortality is still high in Dodoma Regional Referral Hospital. Eclampsia was the leading cause of maternal deaths in 2018 followed by sepsis and obstetric haemorrhage. Delays associated with health system factors (third-phase delay) contributed much more to maternal mortality than the first-phase delay. Mentorship programmes on management of obstetric complications need to be instituted in order to reduce maternal deaths in Dodoma Regional Referral Hospital.